A CRITICAL DISCOURSE ANALYSIS OF FEMINIST LANGUAGE IN OBAMA'S SPEECHES - Al-Ameedi, Riyadh Tariq Kadhum; Khudhair Ashammari, Zina Abdul- Hussein (International Journal of Psychosocial Rehabilitation, 2020)
Feminism is a social and political movement, a theory, and an ideology which concerns itself with women's inferior status in society and educational discrimination due to their sex. It calls for change in all aspects of life whether social, economic, political, or cultural. As a social movement, feminism highlights the different ways women have been oppressed, suppressed and repressed. In this respect, feminism is a movement which has the overall emancipatory aim of redressing gender inequalities in order to create a world in which one gender does not set the standard of human value. As a political movement, feminism has been considered as a revolution which focuses on investigating gender, that is, the way women and men come to construct themselves, their identities and their views of others as more or less feminine or masculine . As a theory , it aims to discover the various reasons behind gender inequalities. As an ideology, it points out to the negative ideas and beliefs that are deeply rooted in societies.